Rental inflation and stabilisation policies: International evidence and the Irish experience - Cathal Coffey; Paul J. Hogan; Kieran McQuinn; Conor O'Toole; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2022)
This research considers the international evidence on the functioning and deployment of measures similar to the Irish "Rent Pressure Zone" (RPZ) framework introduced in late 2016. It also considers how these measures have worked in Ireland in the period from their inception until prior to the COVID-19 pandemic in early 2020 when the maximum allowable rent increase was 4 per cent.
Keywords: 330; Miete; Inflation; Mietenpolitik; Irland; Welt